A bio-based piezoelectric nanogenerator for mechanical energy harvesting using nanohybrid of poly(vinylidene fluoride). Issue 8 (11th July 2019) - Gaur, Anupama; Tiwari, Shivam; Kumar, Chandan; Maiti, Pralay
Abstract : A bio-based nanogenerator for energy harvesting from waste mechanical energy using a nanohybrid of egg shell membrane and polymer. Abstract : A bio-based piezoelectric egg shell membrane (ESM) is used for energy harvesting applications in the form of two and three-component nanohybrids. A bio-waste piezo-filler in a piezoelectric polymer matrix was designed through an induced β-phase nucleation in the matrix using an organically modified two-dimensional nanoclay. Structural alteration (α to β-phase) in the presence of the nanoparticles was also manifested by morphological changes over spherulite to a needle-like morphology; thus, these nanohybrid materials are suitable for energy harvesting applications. ESM-based nanogenerators were fabricated with local ordering of piezo phases, as revealed via atomic force microscopy, leading to the generation of mostly electroactive phases in the whole nanohybrid. The voltage outputs from the optimized device were measured to be ∼56 and 144 V in single and multiple stacks (five), respectively, with corresponding power densities of 55 μW cm −2 and 100 μW cm −2 . The efficiency of the device was verified using a variety of body movements, e.g. bending, twisting, walking, and foot tapping, causing mechanical energy dissipation, which eventually transformed into energy storage. The underlying mechanism of high conversion of energy is explained by the synergistically induced piezo-phase in the polymer matrix together with the floppy piezo-filler. The mechanical stability, durability and repeated energy conversion of the hybrid device make it a robust nanogenerator. The biocompatibility of the nanogenerator was verified through cellular studies, demonstrating its appropriate use in powering biomedical devices/implants.